IMBANGAN KOTORAN KAMBING DAN DAUN BAMBU KERING TERHADAP KARAKTERISTIK KOMPOS - Dicky Ahmad Hezmawan; Nita Opi Ari Kustina; Agustina W. K (Journal of Livestock Science and Production, 2024)
This research aims to determine the characteristics of goat feces compost with the addition of dry bamboo leaves through experiments. The type of research used was experimental using RAL in a unidirectional pattern with 3 treatments and 6 replications. The results of research on P1 showed that the temperature reached an average of 29°C, the water content reached an average of 51,733%, the average color was blackish brown, the average odor was not strong and had an earthy smell, and the texture was smooth. The results of the research on P2 showed that the temperature reached an average of 28°C, the water content reached an average of 49,400%, the average color was brown, the average smell was not strong and had an earthy smell, and had a rough texture. The results of the research on P3 showed the temperature reaches an average of 30°C, the water content reaches an average of 54,400%, the average color is blackish brown, the average smell is strong, and the texture is slightly rough. From these results it can be concluded that the P1 formula produces characteristics that are in accordance with SNI for compost maturity